2 W mm−1 power density of an AlGaN/GaN HEMT grown on free-standing GaN substrate at 40 GHz. (4th November 2019) - Irekti, Mohamed-Reda; Lesecq, Marie; Defrance, Nicolas; Okada, Etienne; Frayssinet, Eric; Cordier, Yvon; Tartarin, Jean-Guy; De Jaeger, Jean-Claude
Abstract: In this letter, a record performance at 40 GHz obtained on an AlGaN/GaN high electron mobility transistor (HEMT) grown on hydride vapor phase epitaxy free-standing GaN substrate is reported. An output power density of 2 W mm −1 associated with 20.5% power added efficiency and a linear power gain ( G p ) of 4.2 dB is demonstrated for 70 nm gate length device. The device exhibits a maximum DC drain current density of 950 mA mm −1 and a peak extrinsic transconductance ( g m Max ) of 300 mS mm −1 at V DS = 6 V. A 100 GHz maximum intrinsic cutoff frequency f T, and a maximum intrinsic oscillation frequency f Max of 125 GHz are obtained from S -parameters measurement. This performance is very promising for HEMTs grown on free-standing GaN substrate.